(untitled) (Dubuque, Iowa, 1975)
The most widely used text for introductory art and design courses, "Art Fundamentals" guides students through both the essential elements of art and the rich and varied history of their uses. This new edition expands the wealth of study materials available to students and faculty by offering a free student CD-ROM and a complete Online Learning Center. Together these new materials help reinforce the principles and elements of design with practical exercises, self-guided tutorials, and interactive examples - without detracting from the central appeal of the text: more colour at a lower price
Keywords: Art,Painting,Sculpture; Technique